Pastoralism 'alive and well' in Africa - Scoones, Ian (International Livestock Research Institute, 2011)
Ian Scoones from the Institute of Development Studies and the Future Agricultures Consortium reflects on some key issues emerging from a recent conference on the future of pastoralism in Africa. His overwhelming conclusion: Pastoralism is "alive and well" in some parts of the continent. But there are downsides: constraints caused by pressures on land, as well as recurring conflicts. This leads to a division between those who are "really making it" and those who are "really struggling." This poses major policy issues at the two ends of these extremes. He also draws attention to Africa-wide developments at the AU and CCADP level where a broad policy framework provides a moment around which issues facing pastoralism can be addressed. In conclusion: "Uncertainty for sure, questions of climate change, uncertain markets, conflict ... but also a positive story and with that a great diversity and the need to attune policies to particular areas and particular places." The Addis Ababa conference (21-23 March 2011) was organized by the Future Agricultures Consortium with Tufts University.